Selection on a Subunit of the NURF Chromatin Remodeler Modifies Life History Traits in a Domesticated Strain of Caenorhabditis elegans - Large, Edward E. (PLoS Genet, 2016)
Evolutionary life history theory seeks to explain how reproductive and survival traits are shaped by selection through allocations of an individual’s resources to competing life functions. Although life-history traits evolve rapidly, little is known about the genetic and cellular mechanisms that control and couple these tradeoffs. Here, we find that two laboratory-adapted strains of C. elegans descended from a single common ancestor that lived in the 1950s have differences in a number of life-history traits, including reproductive timing, lifespan, dauer formation, growth rate, and offspring number. We identified a quantitative trait locus (QTL) of large effect that controls 24%–75% of the total trait variance in reproductive timing at various timepoints. Using CRISPR/Cas9-induced genome editing, we show this QTL is due in part to a 60 bp deletion in the 3’ end of the nurf-1 gene, which is orthologous to the human gene encoding the BPTF component of the NURF chromatin remodeling complex. Besides reproduction, nurf-1 also regulates growth rate, lifespan, and dauer formation. The fitness consequences of this deletion are environment specific—it increases fitness in the growth conditions where it was fixed but decreases fitness in alternative laboratory growth conditions. We propose that chromatin remodeling, acting through nurf-1, is a pleiotropic regulator of life history trade-offs underlying the evolution of multiple traits across different species.